Digital Hadith Reception: The Analysis of Netizen Involvement in the Istimnā' Hadith on the Instagram Account @surgadakwahofc: Resepsi Hadis Digital: Analisis Keterlibatan Netizen terhadap Hadits tentang Istimnā' di Akun Instagram @surgadakwahofc - Syanando Adzikri; Afif Khoirul Hisyam; Ida Rochmawati; Nauval Zhafri (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This study is motivated by the growing phenomenon of religious content dissemination, including hadith, through social media platforms such as Instagram. Although hadiths concerning istimnā’ (masturbation) are frequently cited in online religious discourse, there remains a research gap regarding how digital audiences interpret and respond to such religious texts. Addressing this gap, the present study seeks to answer two main questions: how do netizens receive the hadith on istimnā’ posted on the Instagram account @surgadakwahofc, and what factors influence the diversity of their reception? A qualitative approach was employed using content analysis of netizen comments on posts containing the hadith that prohibits deviant sexual behavior. Stuart Hall’s reception theory served as the analytical framework for identifying audience positions in decoding the religious message, namely, dominant-hegemonic, negotiated, and oppositional readings. The findings reveal that netizen reception is highly diverse and dynamic; some accept the hadith’s meaning textually, others negotiate it according to social context and personal experience, while a few reject it based on rational or modern moral reasoning. This diversity is influenced by social background, level of religious understanding, and individual value orientation. So, the hadith interpretation on social media is a dialogical process involving the interplay between text, context, and audience experience.